The spectacle of feminism and machismo in two Peruvian cumbia singers: Marisol and Tony Rosado - Gutiérrez-Gómez, Edgar; Munaris-Parco, Sonia Beatriz (Frontiers in Sociology, 2023)
The objective of this research is to analyze and interpret the entertainment section of the most important media in Peru, concentrated on two private companies: Grupo La República and Grupo El Comercio, with great journalistic dominance of national information. The entertainment section is as old as the foundation of the newspapers themselves. The method of analysis with qualitative documents has allowed us to reach the conclusion that the fight for gender equality promoted by the government is a spectacle for the national press. The entertainment section of the Peruvian press has exposed the private lives of representative characters such as the singers Marisol, “La Faraona de la Cumbia” and Tony Rosado, “El Ruiseñor de la Cumbia”, from there the differences in feminism tolerated in Marisol and machismo censored in Rosado are popularized. It is concluded that the exposure of the struggle for gender equality is entertainment news where machismo and feminism are underhandedly justified with the parameter established with these public figures, that is, Peruvian cumbia singer–songwriters, and that offers evidence of the tolerance to the feminine voice that incites machismo, justifies the mistreatment of men and makes the male complaint a synonym of cowardice.